Analisis Semiotika Teks Drama Kau Tunggu Siapa, NiloKarya Wisran Hadi - Kartika, Yulia; Asri, Yasnur; Nursaid, Nursaid (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
The purpose of this study were (1) describe the structure of drama texts Kau Tunggu Siapa Nilo Wisran Hadi work, (2) describe the symbols of the elements of literature contained in the text of the drama Kau Tunggu Siapa Nilo Wisran Hadi work, and (3) describe meaning of the symbols contained in the text of the drama Kau Tunggu Siapa Nilo Wisran Hadi work. The method used in analyzing the data are: (1) read and understand the contents of the text of the play in detail, (2) identify the structure of the text contained in the text, (3) inventarisation symbols contained in the text, (4) summarizes the symbols (symbol) and the meaning of the text contained in the drama. Based on data analysis, the conclusion that Drama Kau Tunggu Siapa Nilo Wisran Hadi works have text structure: (1) character, (2) events, (3) conflict, (4) flow, (5) and the background. There are some symbols found in Drama Kau Tunggu Siapa Nilo Wisran Hadi works with words and sentence structures that, if strung together would be similar to the shape of the structure of poetry. Symbols which are capable of clarifying the meaning of the text after the analysis using the approach that is research semiotik. Temuan symbols contained in the text of the drama.